Sickle Cell Anemia: Reference Values of Cerebral Blood Flow Determined by Continuous Arterial Spin Labeling MRI. Issue 2 (1st April 2013) - Arkuszewski, M.; Krejza, J.; Chen, R.; Melhem, E.R.
Sickle cell anemia (SCA) is a chronic illness associated with progressive deterioration in patients' quality of life. The major complications of SCA are cerebrovascular accidents (CVA) such as asymptomatic cerebral infarct or overt stroke. The risk of CVA may be related to chronic disturbances in cerebral blood flow (CBF), but the thresholds of "normal" steady-state CBF are not well established. The reference tolerance limits of CBF can be useful to estimate the risk of CVA in asymptomatic children with SCA, who are negative for hyperemia or evidence of arterial narrowing. Continuous arterial spin labeling (CASL) MR perfusion allows for non-invasive quantification of global and regional CBF. To establish such reference tolerance limits we performed CASL MR examinations on a 3-Tesla MR scanner in a carefully selected cohort of 42 children with SCA (mean age, 8.1±3.3 years; range limits, 2.3–14.4 years; 24 females), who were not on chronic transfusion therapy, had no history of overt stroke or transient ischemic attack, were free of signs and symptoms of focal vascular territory ischemic brain injury, did not have intracranial arterial narrowing on MR angiography and were at low risk for stroke as determined by transcranial Doppler ultrasonography.